2017
DOI: 10.1152/ajplung.00550.2016
|View full text |Cite
|
Sign up to set email alerts
|

TNFα enhances force generation in airway smooth muscle

Abstract: Airway inflammation is a hallmark of asthma, triggering airway smooth muscle (ASM) hyperreactivity and airway remodeling. TNFα increases both agonist-induced cytosolic Ca concentration ([Ca]) and force in ASM. The effects of TNFα on ASM force may also be due to an increase in Ca sensitivity, cytoskeletal remodeling, and/or changes in contractile protein content. We hypothesized that 24 h of exposure to TNFα increases ASM force by changing actin and myosin heavy chain (MyHC) content and/or polymerization. Porci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 65 publications
3
51
0
Order By: Relevance
“…However, hASM sensitivity to muscarinic stimulation is also increased after TNFα, which largely accounts for the enhanced [Ca 2+ ] cyt response, but not the force response (Sieck et al, 2019). In recent studies, we found that the increase in ASM force induced by 24-h TNFα exposure is due to an increase in contractile protein expression (Dogan et al, 2017;Sieck et al, 2019). Importantly, the increase in hASM force generation induced by TNFα exposure is associated with an increase in ATP consumption and tension cost (Dogan et al, 2017).…”
Section: Cytokine Exposure Increases Hasm Force Atp Consumption and mentioning
confidence: 81%
See 4 more Smart Citations
“…However, hASM sensitivity to muscarinic stimulation is also increased after TNFα, which largely accounts for the enhanced [Ca 2+ ] cyt response, but not the force response (Sieck et al, 2019). In recent studies, we found that the increase in ASM force induced by 24-h TNFα exposure is due to an increase in contractile protein expression (Dogan et al, 2017;Sieck et al, 2019). Importantly, the increase in hASM force generation induced by TNFα exposure is associated with an increase in ATP consumption and tension cost (Dogan et al, 2017).…”
Section: Cytokine Exposure Increases Hasm Force Atp Consumption and mentioning
confidence: 81%
“…In previous studies, we showed that 24-h exposure of hASM cells to TNFα increases both [Ca 2+ ] cyt and force responses to 1 µM muscarinic (ACh) stimulation (White et al, 2006;Sathish et al, 2009Sathish et al, , 2011Delmotte et al, 2012;Jia et al, 2013;Delmotte and Sieck, 2015;Dogan et al, 2017;Sieck et al, 2019). However, hASM sensitivity to muscarinic stimulation is also increased after TNFα, which largely accounts for the enhanced [Ca 2+ ] cyt response, but not the force response (Sieck et al, 2019).…”
Section: Cytokine Exposure Increases Hasm Force Atp Consumption and mentioning
confidence: 94%
See 3 more Smart Citations